Carbon protection and fire risk reduction: toward a full accounting of forest carbon offsets - Hurteau, Matthew D; George W Koch; Bruce A Hungate (Frontiers in ecology and the environment, 2008)
Management of forests for carbon uptake is an important tool in the effort to slow the increase in atmospheric COâ and global warming. However, some current policies governing forest carbon credits actually promote avoidable COâ release and punish actions that would increase longâterm carbon storage. In fireâprone forests, management that reduces the risk of catastrophic carbon release resulting from standâreplacing wildâfire is considered to be a COâ source, according to current accounting practices, even though such management may actually increase longâterm carbon storage. Examining four of the largest wildfires in the US in 2002, we found that, for forest land that experienced catastrophic standâreplacing fire, prior thinning would have reduced COâ release from live tree biomass by as much as 98%. Altering carbon accounting practices for forests that have historically experienced frequent, lowâseverity fire could provide an incentive for forest managers to reduce the risk of catastrophic fire and associated large carbon release events.